Growth performance and feed conversion efficiency of three edible mealworm species (Coleoptera: Tenebrionidae) on diets composed of organic by-products. (February 2015) - van Broekhoven, Sarah; Oonincx, Dennis G.A.B.; van Huis, Arnold; van Loon, Joop J.A.
Abstract : Graphical abstract: Highlights: Three edible mealworm species were grown on diets composed of organic by-products. High protein diets appeared favourable in terms of larval growth and survival. Feed conversion was more efficient on high protein diets. Mealworm protein showed to be stable on various diets, whereas fat content varied. Abstract: Insects receive increasing attention as an alternative protein-rich food source for humans. Producing edible insects on diets composed of organic by-products could increase sustainability. In addition, insect growth rate and body composition, and hence nutritional quality, can be altered by diet. Three edible mealworm species Tenebrio molitor L., Zophobas atratus Fab. and Alphitobius diaperinus Panzer were grown on diets composed of organic by-products originating from beer brewing, bread/cookie baking, potato processing and bioethanol production. Experimental diets differed with respect to protein and starch content. Larval growth and survival was monitored. Moreover, effects of dietary composition on feed conversion efficiency and mealworm crude protein and fatty acid profile were assessed. Diet affected mealworm development and feed conversion efficiency such that diets high in yeast-derived protein appear favourable, compared to diets used by commercial breeders, with respect to shortening larval development time, reducing mortality and increasing weight gain. Diet also affected the chemical composition of mealworms. Larval protein content was stable on diets that differed 2–3-fold in protein content, whereas dietary fat did have an effect on larval fat content and fatty acid profile. However, larval fatty acid profile did not necessarily follow the same trend as dietary fatty acid composition. Diets that allowed for fast larval growth and low mortality in this study led to a comparable or less favourable n6/n3 fatty acid ratio compared to control diets used by commercial breeders. In conclusion, the mealworm species used in this study can be grown successfully on diets composed of organic by-products. Diet composition did not influence larval protein content, but did alter larval fat composition to a certain extent.